Agroecosystem management strategies and trophic interactions among herbivores, pathogens and predators - Perez, André Lage (2016)
Reducing the environmental complexity and increasing biomass of cultivated plants offer favorable conditions for pest species in conventional systems. Among biological control strategies, the restoration of vegetation diversity in agroecosystems and the adoption of management strategies aiming to reduce impacts on natural enemy populations are practices that can be employed in different types of farming systems. Much of the conservative biological control efforts are focused on maintaining populations of parasitoids and predators. However, pathogens represent key mortality factors in the regulating pest populations in crops. The maintenance of indigenous plants aiming to increment populations of predators and parasitoids, may also promote the preservation of propagules of entomopathogenic fungi in the soil. In addition, the reduction of soil disturbance may reduce impacts on the entomopathogenic community in agroecosystems soil. Studiyng the ecological interactions between predators, pathogens and herbivores is a key factor in understanding the role of biological control of pests in agroecosystems. As a model of crop management practices and conservative biological control strategies we used chili pepper crops (Capsicum frutescens) and melon (Cucumis melo var cantalupensis) represented by small fields and high susceptibility to pests. Interactions between natural enemies were studied in microcosms in greenhouse. Therefore, the goal of this thesis was to evaluate the role of agro-ecosystems management practices as biological control strategies of pests in annual crops. Aim is also to study in detail the ecological interactions between natural enemies, herbivores and plants. From this framework we addressed the following hypothesis: a) Non-crop plants promote the modification of biotic and abiotic factors affecting virulence, occurrence and abundance of entomopathogenic fungi in the soil; b) the use no-tillage in annual crops performs the preservation of entomopathogens in the soil resulting in higher virulence and occurrence of microorganisms in agroecosystems; c) herbivores exposed to spores of entomopathogenic fungi reduce their herbivory on the host plant; d) the exposure of herbivore to pathogen spores affect predation; e) herbivores reduce and modulate feeding behavior in the presence of a predator; f) joint action of pathogen and predator results in a further reduction in the damage caused by herbivores to plants. As a result we found that the maintenance of non-crop plants in chili pepper crops is not an effective as a short-term strategy for preserving entomopathogenic fungi. The fungal virulence in two experimental fields with non- crop plants was higher than in chili pepper monoculture, but in one field we observed an inverse result for fungi virulence. The tillage regime in melon crops did not affect the virulence of soil-borne entomopathogens. The occurrence and virulence of entomopathogens was affected by sampling time during the growing season, showing a time-scale pattern of entomopathogenic dynamics in agroecosystems. In laboratory assay and in the greenhouse we observed that spiders do not show preferential predation for prey exposed to the pathogen. The exposure to spores of pathogen did not reduce the herbivory D. undecimpunctata on melon plants, however the presence of predator reduced the damage caused by the herbivore, both due predation and reduce time allocated by beetle on the plant. Also, we observed that herbivores exposed to pathogen and in the presence of predator damaged the plants in a similar rate compared to beetles in the absence of any natural enemy (predators or pathogen). In conclusion, from the results obtained in this thesis, it is concluded that the use of habitat management strategies should pay attention not only to the landscape composition and reduced disturbances but especially the time factor restore ecosystem services performed by entomopathogens. We also concluded that pathogens, predators, herbivores and plants have trophic interactions that differentially affect the dynamics of natural enemies and their ecosystem services.